Primary progressive aphasia: analisys of 16 cases - Márcia Radanovic; Mirna Lie Hosogi Senaha; Letícia Lessa Mansur; Ricardo Nitrini; Valéria Santoro Bahia; Maria Teresa Carthery; Flávia Nóbrega Freire Aires; Sandra Christina Mathias; Paulo Caramelli (Arquivos de Neuro-Psiquiatria)
Primary progressive aphasia (PPA) is an intriguing syndrome, showing some peculiar aspects that differentiate it from classical aphasic pictures caused by focal cerebral lesions or dementia. The slow and progressive deterioration of language occurring in these cases provides an interesting model to better understand the mechanisms involved in the linguistic process. We describe clinical and neuroimaging aspects found in 16 cases of PPA. Our patients underwent language and neuropsychological evaluation, magnetic resonance imaging (MRI) and single photon emission computerized tomography (SPECT). We observed a clear distinction in oral expression patterns; patients were classified as fluent and nonfluent. Anomia was the earliest and most evident symptom in both groups. Neuroimaging pointed to SPECT as a valuable instrument in guiding the differential diagnosis, as well as in making useful clinical and anatomical correlations. This report and a comparison to literature are an attempt to contribute to a better understanding of PPA.